Trevally of the Spermonde Archipelago, South Sulawesi - Andi Iqbal Burhanuddin; Andi Evi Erviani (Hasanuddin University, 2016)
The Carangoidae, popularly known as trevally is a commercially fishes and one of marine resources abundance in water of Indonesia. A study has been carried out to describethe carangoid fishes of the family Carangidae from the Spermonde Archipelago, South Sulawesi and the result will be used as basis for further study especially on bio-diversity monitoring for the area. This study was conducted from August 2006to November 2015. Thirty carangoid fishes belonging 13 genera were examined and identified: Alepes, Alectis, Atule, Decapterus, Caranx, Carangoides, Elagatis, Gnathanodon, Megalaspis, Pseudocaranx, Scomberoides, Selar, and Selaroides. The Common name available of each species was given.